DETERMINAN TERJADINYA FRAUD DI INSTANSI PEMERINTAHAN (PERSEPSI PADA PEGAWAI BPK RI PERWAKILAN PROVINSI NTB) - Wulandari, Susi; Zaky, Achmad (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to examine the influence of leadership style, appropriateness compensation, the effectiveness of the internal control system, law enforcement, ethical organizational culture and organizational commitment to fraud in government agencies. The dependent variable used in this study is fraud in government agencies, while independent variables used are leadership style, appropriateness compensation, the effectiveness of the internal control system, law enforcement, ethical organizational culture and organizational commitment. This study used 51 respondents at Audit Board of Republic Indonesia Representative office of Nusa Tenggara Barat (NTB) with census method. Data analysis method used is multiple linear regression statistical analysis. Results of regression analysis found that the appropriateness of compensation, the effectiveness of internal control systems, and organizational commitment influence on fraud  in  government  agencies,  while  the  leadership  style,  law  enforcement,  and  the ethical organizational culture are not affect the occurrence of fraud in government agencies. The most dominant factor of influence on the occurrence of fraud is the effectiveness of the internal control system.   Keywords: Fraud, government agencies, leadership style, appropriateness compensation, internal control system, ethical organizational culture, organizational commitment